Research on the impact of urban innovation on public health - Zhao, Liang; Li, Chen; Qian, Yaosen (Frontiers in Public Health, 2025)
IntroductionThis article explores the impact of innovation on urban public health, with a particular focus on panel data from 15 sub-provincial cities in China. The study aims to provide scientific evidence for policymakers by analyzing how technological innovation affects urban public health levels.MethodsThe study used a panel model for empirical analysis which based on panel data from 15 sub provincial cities across the country, using the number of doctors per 10,000 people and per capita financial medical and health expenditure as proxy variables for urban public health, and using the level of technological development as the core explanatory variable for regression analysis.ResultsThe research results show that: (1) for public health quantified by the number of doctors per 10,000 people in cities, innovation does not have a significant promoting effect on urban public health; (2) Compared to the number of doctors per 10,000 people in a region, the per capita financial expenditure on healthcare can better measure the level of urban public health; (3) Innovation has a significant impact on urban public health, measured by per capita fiscal expenditure on healthcare.DiscussionIn order to transform technological innovation into a driving force for the development of urban public health, efforts must be made from multiple aspects. Currently, building a strong foundation for people’s health relies on the support of science and technology, and enhancing innovation as a primary driving force is crucial. China urgently needs to improve the stability and competitiveness of its pharmaceutical industry and supply chain, break through key core technologies, and take the initiative in the future development of the pharmaceutical industry.